Japanese Writers and Works on Djawa Baroe: Behind the Selection of the Five Works - Anwar, Fithyani (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Literature became one of the propaganda tools of the Japanese military government during the Japanese occupation of Indonesia (1942-1945). This research focuses the object of study on four short stories and one play written by Japanese writers published in Djawa Baroe magazine (1943-1945), including "Kitjizo Kemedan Perang" by Hino Ashihei, "Ditempat Asoehan Garoeda" by Niwa Fumio, "Batoe" by Kawai Tetsukichi and "Perkawinan 25 Tahoen" by Sasaki Takamaru. The qualitative descriptive method was used to analyze data on each writer's background and the original versions published in Japan to examine the reasons and significance for selecting the five works. The findings show that four writers, Hino Ashihei, Niwa Fumio, Kikuchi Kan, and Sasaki Takamaru, had produced many works and were well-known writers in Japan. Meanwhile, Kawai Tetsukichi was a newcomer writer, but his work "Batoe" was considered new and attracted the editor of Chūōkōron magazine. Furthermore, research on the original versions of the five works published in Japan discovers that all five works were published in Japan between 1938 and 1943 and then republished in Djawa Baroe from January 1, 1944, to March 15, 1944. Some original works are short and almost the same as those published in Djawa Baroe, but some were long novels, so only small parts were published in Djawa Baroe.  However, the versions published in Djawa Baroe contained significant propaganda parts of each work and were suitable for Djawa Baroe's readers during the war. The writer`s reputation and the contents of each work were the main reasons the works were selected for publication in Djawa Baroe.  Keywords: Djawa Baroe, Japanese literature, Japanese Writer, Asia-Pacific War